Perancangan E-Rekam Medis pada Pelaporan Pemakaian Darah Pasien Hemodialisa dengan Metode Agile - Anasya Intania Permata; Syahidin, Yuda; Suryani, Ade Irma (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
Chronic renal failure is a serious kidney disorder that can lead to a high risk of death, chronic renal failure causes 850,000 deaths every year. This study aims to produce an electronic-based reporting information system on reporting the blood usage of hemodialysis patients. In kebonjati bandung hospital, there are problems in reporting the blood usage of hemodialysis patients, which until now still use manual reporting. This research uses qualitative descriptive research used to gain a better understanding of the research topic. Researchers use methods such as observation, interviews, and analysis of relevant documents to collect data. A software development method called the agile method is used in this research. The creation of the information system design model was made using visual studio 2010 with an access database system and the system was tested using black-box. The results of the information system created can help facilitate officers in minimizing the time of filling in the data needed to produce efficient reports.